Low serum albumin levels prior to pediatric allogeneic HCT are associated with increased need for critical care interventions and increased 6‐month mortality. (2nd July 2017) - Teagarden, Alicia M.; Skiles, Jodi L.; Beardsley, Andrew L.; Hobson, Michael J.; Moser, Elizabeth A. S.; Renbarger, Jamie L.; Rowan, Courtney M.
Abstract: Poor nutritional status in HCT patients is a negative prognostic factor. There are no pediatric studies evaluating albumin levels prior to HCT and need for critical care interventions. We hypothesized that pediatric patients with low albumin levels, routinely measured 30 days (±10 days) prior to allogeneic HCT, have a higher risk of critical care interventions in the post‐transplant period. We performed a 5‐year retrospective study of pediatric patients who underwent allogeneic HCT for any indication. Patients were categorized based on albumin level. Hypoalbuminemia was defined as <3.1 g/dL. A total of 73 patients were included, with a median age of 7.4 years (IQR 3.3, 13.2). Patients with hypoalbuminemia had higher needs for critical care interventions including non‐invasive ventilation (44% vs 8%, P =.01), mechanical ventilation (67% vs 17%, P <.01), and vasoactive therapy (56% vs 16%, P =.01). Patients with hypoalbuminemia also had a higher 6‐month mortality (56% vs 17%, P =.02). Our data demonstrate that children undergoing allogeneic HCT with hypoalbuminemia in the pretransplant period are more likely to require critical care interventions and have higher 6‐month mortality. These findings identify an at‐risk population in which nutritional improvements may be instituted prior to HCT in hopes of improving outcomes.